Pengaruh Aktivitas Penambangan Batu Granit terhadap Kualitas Air Sungai: (Studi Kasus: Sungai Ambaepea Desa Mata Wawatu, Kecamatan Moramo Utara, Kabupaten Konawe Selatan) - Ardi, Muh. Ardiansyah; Assiddieq, Moch.; Adami, Aryani (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
The exploitation of mineral resources or minerals, such as granite mining, is one of the main pillars of the development sector from physical, economic and social aspects. However, it cannot be denied that improperly managed mining has the potential to cause negative environmental impacts. On the other hand, the life of aquatic biota is highly dependent on the condition and quality of water physically, chemically and biologically. This study aims: (1) To determine the granite mining activities on the banks of the Ambaepea River located in Mata Wawatu Village. (2) To determine the effect of granite mining activities on the quality of pH, TSS, lime, and water temperature in the Ambaepea River. The analysis of Ambaepea River water samples was carried out in two laboratories, namely at the Environmental Engineering Laboratory, Faculty of Engineering, Muhammadiyah University Kendari and at the Biomolecular and Environmental Laboratory, Faculty of Mathematics and Natural Sciences, Haluoleo University Kendari. The research results showed that the pH level obtained at sample point I was 6 and at sample point II was 7. The TSS level obtained at sample point I was 93,33 mg/L and at sample point II the TSS level obtained was 2580,33 mg/L. The lime content (CaCO3) obtained at sample point I was 189,60 mg/L and at sample point II the lime content obtained was 495,20 mg/L. The temperature level obtained at sample point I was 27°C with an air temperature of 29°C and at sample point II the temperature obtained was 26°C with an air temperature of 29°C. The average deviation of water temperature and ambient temperature at sample point I was 2 and at sample point II the average water and ambient temperature deviation obtained was 3.